In search of answer to the question - Do teachers from grammar schools shape their pupils' ecologically friendly attitude? - Stańczak, Małgorzata (Studia Ecologiae et Bioethicae, 2008)
In order to survive humankind needs ecological education in accordance with the rule of well-balanced development. The phenomenon involves all educational processes. We need well-qualified teachers in order to mobilize pupils for proper action, influence their interests and higher level of knowledge or shape ecological awareness, these teachers link the world of thoughts and general consciousness. The present study is the attempt to answer the question - Do teachers from grammar schools shape their pupils’ ecologically friendly attitude?